Persepsi Masyarakat Terhadap Pengembangan Ekowisata Hutan Adat Berbasis Kearifan Lokal - Riyan Hermawan; Niechi Valentino; Endah Wahyuningsih (Ulul Albab: Majalah Universitas Muhammadiyah Mataram, 2026)
This study aims to analyze community perceptions and the factors influencing the proposed development of community-based ecotourism in the customary forest of Bayan Village, North Lombok. The study employed a quantitative approach using a descriptive research design and multiple linear regression analysis. Data were collected through a Likert-scale questionnaire administered to 100 respondents from the local community of Bayan Village, North Lombok. The research instrument comprised four dimensions of ecotourism development: tourism attractions (4 items), accessibility (3 items), amenities (7 items), and institutional aspects (5 items). Data were analyzed using Microsoft Excel and IBM SPSS software. The findings indicate that the community holds a highly positive perception of the proposed ecotourism development, with an average agreement rate of 98%, particularly regarding tourism attractions, accessibility, amenities, and institutional support. These results demonstrate strong support from the indigenous community for ecotourism development as a sustainable strategy capable of generating ecological, social, and economic benefits while preserving the local wisdom and cultural heritage that have been passed down through generations.